Francoist repression, genocidal violence or coercive violence? An analysis from the local history in southwestern Spain - Martínez Gálvez, José Carlos (Hispania Nova, 2021)
This study aims to test whether the term genocide, or any synonym, can be appropriately used to describe, from the perspective of practical research, the violent activities carried out around a village in southwestern Spain following the military coup in 1936. It takes into consideration the case of those who opted to surrender as well as those who stood in opposition. Following the documents analyzed, the author points out the main problems this type of characterization cause and how, given the main characteristics of this violence, it better corresponds to the coercive violence that tends to take place in contexts of mass violence, such as a civil war.
Keywords: genocidal violence; coercive violence; holocaust; extermination; francoist violence; Civil War